Juridical Analysis of Consumer Protection Against Beauty Cosmetics That Are Not Fit for Distribution (Study at the Food Drug Supervisory Agency BPOM Bandar Lampung) - Putri, Tiara Susilo; Anggalana, Anggalana; Hesti, Yulia (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
A common form of abuse in the Cosmetics and Skincare sector is the use of dangerous ingredients added to illegal Cosmetics and Skincare products. The aim of this research is as follows: To find out, understand and analyze consumer legal protection for beauty cosmetics that are not fit for distribution (Study at the Food Drug Supervisory Agency BPOM Bandar Lampung). To find out, understand and analyze Indonesian legal regulations regarding beauty cosmetics that are not fit for distribution (Study at the Food Drug Supervisory Agency BPOM Bandar Lampung). The problem approach that will be used in this research is a normative juridical approach and an empirical approach. The results of the research show that consumer legal protection for beauty cosmetics that are not fit for distribution (BPOM Bandar Lampung study center), namely by doing 2 (two) things, the first is to tighten the licensing process as a form of protection for consumers.